2001
DOI: 10.1097/00001756-200107030-00053
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chemokines and chemokine receptors after experimental closed head injury

Abstract: The expression of the chemokines macrophage inflammatory protein (MIP)-2 and MIP-1alpha and of their receptors CXCR2 and CCR5 was assessed in wild type (WT) and TNF/lymphotoxin-alpha knockout (TNF/LT-alpha-/-) mice subjected to closed head injury (CHI). At 4 h after trauma intracerebral MIP-2 and MIP-1alpha levels were increased in both groups with MIP-2 concentrations being significantly higher in WT than in TNF/LT-alpha-/- animals (p < 0.05). Thereafter, MIP-2 production declined rapidly, whereas MIP-1alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 22 publications
0
31
1
Order By: Relevance
“…A prominent chemokine receptor implicated in resident microglial migration in the literature is CCR5. It has been shown to be constitutively expressed in resting microglia (Simpson et al, 2000;Otto et al, 2001) and upregulated in diverse pathological states (Mennicken et al, 2002;Glabinski et al, 2003;Natale et al, 2003). Additionally, many CCR5 ligands such as MIP-1␣/CCL3, MIP-1␤/CCL4, and RANTES/CCL5 are released after neural injury (Ghirnikar et al, 1996;Babcock et al, 2003;Marella and Chabry, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prominent chemokine receptor implicated in resident microglial migration in the literature is CCR5. It has been shown to be constitutively expressed in resting microglia (Simpson et al, 2000;Otto et al, 2001) and upregulated in diverse pathological states (Mennicken et al, 2002;Glabinski et al, 2003;Natale et al, 2003). Additionally, many CCR5 ligands such as MIP-1␣/CCL3, MIP-1␤/CCL4, and RANTES/CCL5 are released after neural injury (Ghirnikar et al, 1996;Babcock et al, 2003;Marella and Chabry, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Other possible chemokine receptor candidates include CCR1, CCR3, CX3CR1, and CXCR3 (Maciejewski-Lenoir et al, 1999;Bajetto et al, 2002;Flynn et al, 2003); however, relative contributions likely depend on injury stimulus. The intrinsic chemokines for CCR5 have been studied previously after stab lesion (Ghirnikar et al, 1996) and in other injury models (Baker et al, 1999;Otto et al, 2001;Babcock et al, 2003;Marella and Chabry, 2004). A candidate common to all models is RANTES/CCL5.…”
Section: Discussionmentioning
confidence: 99%
“…Using the ependymal route, described by Martino et al (26), allows vectors to distribute throughout cerebrospinal fluid (CSF) and infect ependymal and leptomeningeal cells, which in turn secrete the product of the transgene into the CSF. This route avoids the traumatic effects of tissue injury associated with intraparenchymal and intracerebroventricular injections, which can include chemokine production and disruption of the blood-brain barrier (27)(28)(29)(30).…”
Section: Ifn-␥-induced Chemokines Synergize With Pertussis Toxin To Pmentioning
confidence: 99%
“…However, AdIFN␥ did not induce expression beyond baseline levels of other chemokines, including CXCL2, CCL2/ MCP-1, or CCL3/MIP-1␣ (data not shown). These chemokines have been implicated in CNS inflammatory responses (25,30,39,40), and their absence in this system suggests that other signals in addition to IFN-␥ are required for immune pathology.…”
Section: Intrathecal Ifn-␥ Induces Selective Chemokine Expression In Cnsmentioning
confidence: 99%
“…These findings confirm the historic notion that lymphocytes do not represent important effector cells of the immunological response to TBI, in contrast to neutrophils and monocytes/macrophages, and activated microglia (Bellander et al, 2010;Biagas et al, 1992;Ramlackhansingh et al, 2011;Rhodes, 2011;SzmydyngerChodobska et al, 2011). In fact, we have shown that neutrophils infiltrate the injured brain within 24 h in the present model of closed head injury in mice, and that cellular infiltration is largely regulated by chemokines and chemokine receptors expressed by neutrophils, macrophages, and resident cells of the CNS (Otto et al, 2001;Stahel et al, 2000). The only relevant differences in outcome parameters analyzed in this study consisted of significantly attenuated serum levels of the complement activation fragment C3a (Fig.…”
Section: Closed Head Injury In Immunodeficient Rag1mentioning
confidence: 56%